ANALISIS KOHESI GRAMATIKAL DALAM BERITA ONLINE CNNINDONESIA.COM PADA RUBRIK NASIONAL EDISI OKTOBER 2019 - Arief Dwi Ashari; Ika Maiatun Khasanah; Salma Hanifah (Universitas Sarjanawiyata Tamansiswa, 2019)
The research aims to expose grammatical cohesion in the online news cnnindonesia.com on the National rubric of October 2019 edition. This method of research uses a qualitative descriptive approach. The technique used for data retrieval in this research is the technique of reading and note-taking. The subject of this research is the discourse of online news cnnindonesia.com on the National rubric of October 2019 edition. This research is focused on the form of grammatically cohesion markers. The result of this research is that of the 10 news analyzed found 52 data. The grammatical markers contained in the data are references, substitutions, ellipses, and conjunctions. Conjunctions and references are the most widely found type of grammatical cohesion